2008
DOI: 10.1073/pnas.0710811105
|View full text |Cite
|
Sign up to set email alerts
|

Invasive plants transform the three-dimensional structure of rain forests

Abstract: Biological invasions contribute to global environmental change, but the dynamics and consequences of most invasions are difficult to assess at regional scales. We deployed an airborne remote sensing system that mapped the location and impacts of five highly invasive plant species across 221,875 ha of Hawaiian ecosystems, identifying four distinct ways that these species transform the three-dimensional (3D) structure of native rain forests. In lowland to montane forests, three invasive tree species replace nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
181
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 245 publications
(199 citation statements)
references
References 23 publications
9
181
1
1
Order By: Relevance
“…Invasive plants are a subset of naturalized plants that produce offspring, often in very large numbers, at considerable distances from the parent plants, and thus have the potential to spread over a large area (Richardson et al 2000, Pyšek et al 2004. Although an analysis of the Global IUCN Red List by Gurevitch and Padilla (2004) suggested that invasive species are not the main cause of decline of native endangered species, some invasive plants can alter ecosystems and decrease biodiversity of the native species by dominating habitats (Richardson 1998, Lowe et al 2000, Yoshida and Oka 2004, Asner et al 2008. These invasive plants that change the character, condition, form, or nature of ecosystems over substantial areas are known as "transformers" (Richardson et al 2000, Pyšek et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive plants are a subset of naturalized plants that produce offspring, often in very large numbers, at considerable distances from the parent plants, and thus have the potential to spread over a large area (Richardson et al 2000, Pyšek et al 2004. Although an analysis of the Global IUCN Red List by Gurevitch and Padilla (2004) suggested that invasive species are not the main cause of decline of native endangered species, some invasive plants can alter ecosystems and decrease biodiversity of the native species by dominating habitats (Richardson 1998, Lowe et al 2000, Yoshida and Oka 2004, Asner et al 2008. These invasive plants that change the character, condition, form, or nature of ecosystems over substantial areas are known as "transformers" (Richardson et al 2000, Pyšek et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive species (IS) pose a significant threat to native biodiversity, habitat, and ecosystem functioning (Vitousek et al 1996, Asner et al 2008, Pyšek and Richardson 2010. IS have led to reductions in native species richness (Gaertner et al 2009) and half of vertebrate extinctions on island ecosystems in the past century (Tershy et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Non-native invasive plant species are major threats to ecosystem structure and function (Asner et al 2008;Hejda et al 2009;Vitousek et al 1987;Wilcove et al 1998). Patterns of invasion result from a combination of species' traits, propagule pressure and variation in the local environment and surrounding landscape (Eschtruth and Battles 2011;Kumar et al 2006;Lonsdale 1999).…”
Section: Introductionmentioning
confidence: 99%